2015
DOI: 10.24191/jeeir.v3i1.9046
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Change in Pakistan Commercial Banking Sector: A Pre and Post Digital-Restructuring Analysis

Abstract: In this study we examine the technical efficiency of commercial banking sector of Pakistan. In recent past Pakistan’s commercial banking is making substantial investment and up-gradation in information and communication technology (ICT) in order to keep pace with global banking industry. Due to financial linearization the entry of the foreign banks with advance technology in the commercial banking sector has been increased that inclines other banks to adopt the new technology in order to earn more of market sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, the effect on company performance is not more significant compared to digital technology and marketing capabilities. The results support the previous researchers' opinions [14,21,26,39,40]. In this case, the role of digital leadership is very important in encouraging the successful implementation of digital technology in the company's work processes.…”
Section: B Evaluation Of Structural Model (Inner Model)supporting
confidence: 89%
See 2 more Smart Citations
“…However, the effect on company performance is not more significant compared to digital technology and marketing capabilities. The results support the previous researchers' opinions [14,21,26,39,40]. In this case, the role of digital leadership is very important in encouraging the successful implementation of digital technology in the company's work processes.…”
Section: B Evaluation Of Structural Model (Inner Model)supporting
confidence: 89%
“…Then, previous research measures the changes in efficiency in Pakistan's commercial banking sector by analyzing pre-and post-digital restructuring. The research results show that there has been a significant increase in technical efficiency in the post-digital reform era [14]. Likewise, digital marketing increases competitiveness and service delivery to its customers [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results indicate a positive efficiency improvement in the commercial banking industry. Mustafa and Mehmood (2015) measured the efficiency and productivity change for few numbers of CBs of Pakistan and compare the efficiency change of pre-digital and post-digital periods. To measure the efficiency of conventional and Islamic banking in Pakistan, Saeed, Ali, Adeeb, and Hamid (2013) found that conventional banking performance is relatively better than Islamic banking in terms of operational efficiency for the specific time period.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They argue that ITintensive industries in USA have not even registered a fast growth as compared to non-IT-intensive industries and there is a very minute productivity growth in such industries. Mustafa and Mehmood (2015) reported that technical efficiency and total factor productivity of banks in Pakistan have been significantly increased in post-digital reform era. Lee, et al (2016) suggested that seeing constant upsurges in IT investment, the IT itself cannot create value rather what matters is the way IT is employed to generate business outcomes.…”
Section: Literature Review and Hypothesismentioning
confidence: 99%